(3GdTaGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3aUhd GdebGdI GdChdi KeGfjI aUhd GdaUd GdChd ai GHJOGA WdH ehVhY GdadSaI GdChdi s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg ajLH Ef JfUQa Edi GdZQV GdPi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1055s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdadSaI hGdefWbs